Sengketa Pembiayaan Akad Murabahah: Analisis Komparasi - Supardin, Muhammad Ikhlas; JM Muslimin, (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2022)
This study aims to analyze comparation of the South Jakarta Religious Court in deciding cases no. 1957/Pdt.G/2018/PA.JS and no. 407/Pdt.G/2019/PA.JS. This research based on normative legal, known as doctrinal legal research. The approaches used in this study were the statute approach, case approach and comparative approach. The results of this study indicate that the two decisions are based on legal considerations by the judge by referring to legal arguments and related laws. The judge granted the plaintiff's request in decision no. 1957/Pdt.G/2018/Pa.Js. Otherwise the decision no. 407/Pdt.G/2019/Pa.Js, the judge rejected the plaintiff's application in its entirety. Both of decisions are included in the case of deffered payment financing, but there are differences in the legal considerations by the judges of the South Jakarta Court so that there are different decision. Keywords: Dispute Settlement; Deffered Payment Financing; Religious Court Decision